Recombinant Leishmania infantum Heat Shock Protein 83 for the Serodiagnosis of Cutaneous, Mucosal, and Visceral Leishmaniases - Celeste, Beatriz Julieta (The American Society of Tropical Medicine and Hygiene, 2014)
Routine serological diagnoses for leishmaniases, except in visceral cases, are performed using whole-parasite antigens. We used enzyme-linked immunosorbent assay (ELISA) to evaluate the performance of Leishmania infantum rHsp83 compared with L. major-like total promastigote antigen in the diagnosis of cutaneous (CL), mucosal (ML), and visceral leishmaniases (VL). ELISA-rHsp83 was significantly more sensitive than ELISA–L. major-like when considering either CL/ML (P = 0.041) or all leishmaniasis patients (P = 0.013). When samples from other infectious disease patients were evaluated for cross-reactivity, ELISA-rHsp83 was more specific than ELISA–L. major-like, specifically for Chagas disease samples (P < 0.001). We also evaluated the anti-rHsp83 antibody titers months after treatment and observed no significant difference in ML (P = 0.607) or CL (P = 0.205). We recommend ELISA–L. infantum-rHsp83 as a routine confirmatory serological assay for the diagnosis of Leishmania infection because of the high sensitivity, the specificity, and the insignificant cross-reactivity with other infectious diseases.